2016
DOI: 10.1017/s0033291715002081
|View full text |Cite
|
Sign up to set email alerts
|

Somatic, positive and negative domains of the Center for Epidemiological Studies Depression (CES-D) scale: a meta-analysis of genome-wide association studies

Abstract: Background Major depressive disorder (MDD) is moderately heritable, however genome-wide association studies (GWAS) for MDD, as well as for related continuous outcomes, have not shown consistent results. Attempts to elucidate the genetic basis of MDD may be hindered by heterogeneity in diagnosis. The Center for Epidemiological Studies Depression (CES-D) scale provides a widely used tool for measuring depressive symptoms clustered in four different domains which can be combined together into a total score but al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…However, due to the logistical difficulties inherent in assessing sleep architecture in large samples of adolescents, data on the link between depressive symptoms and REM fragmentation are scarce. The current study explored how REM sleep fragmentation, density, and latency are related to self-reported depressive symptoms and to a genetic predisposition to depression, using an adolescent birth cohort and a polygenic risk score (PRS) derived from a recent genome-wide association study (GWAS) for depressive symptoms (Demirkan et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, due to the logistical difficulties inherent in assessing sleep architecture in large samples of adolescents, data on the link between depressive symptoms and REM fragmentation are scarce. The current study explored how REM sleep fragmentation, density, and latency are related to self-reported depressive symptoms and to a genetic predisposition to depression, using an adolescent birth cohort and a polygenic risk score (PRS) derived from a recent genome-wide association study (GWAS) for depressive symptoms (Demirkan et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…We performed a weighted polygenic risk score (PRS) analysis using betas from GWAS summary statistics data of CHARGE Consortium GWAS for dimensions of depressive symptoms (Demirkan et al 2016). The dimensions were three subscales from The Center for Epidemiologic Studies Depression Scale (CES-D), namely negative emotion, lack of positive emotion, and somatic complaints.…”
Section: Polygenic Risk Scores For Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CES-D scale was developed to diagnose depression by way of assessing a range of depressive symptoms. This scale is a widely used measure of depression and several short CES-D forms have been developed from it [30, 31]. Each item was answered using a 4-point scale (0 = less than one day in the past week; 1 = two or three days in the past week; 2 = four or five days in the past week; 3 = six or seven days in the past week).…”
Section: Methodsmentioning
confidence: 99%
“…According to the subsequent genome-wide association studies, SNPs residing the genes involved in circadian rhythms regulation such as sirtuin 1 (SIRT1), melatonin receptor 1A gene (MTNR1A), fragile histidine triad (FHIT) (CONVERGE consortium, 2015;Demirkan et al, 2016;Direk et al, 2017) are of interest. These findings suggest a significant role of circadian rhythms in the regulation of individual psychoemotional sphere and point to the necessity to consider them in the DD research for the understanding of biological mechanisms causing this affective disorder.…”
Section: Genome-wide Association Study (Gwas)mentioning
confidence: 99%